Pemerintahan dalam Perspektif Al-Quran - Fahrul Abd. Muid (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2010)
Governmental is very important for a community of nations, because the government guarantee an orderly system of life will be realized. In Islam, it is widely known the term Ã¢â‚¬Å“al-siyasah al-syarÃ¢â‚¬â„¢iyyahÃ¢â‚¬Â (religious politics) and formal leadership are so-called caliphate, sultan, Imamat, and uli al-amr. The QurÃ¢â‚¬â„¢an does not specify a particular form and style of government for Muslims; therefore, they have the freedom to choose the form of government. The Qur'an only contains the basic values of ethics and political morality as a foundation of a state or a nation. Government (khalifah), in carrying out development tasks should refer to its functions and duties as the khalifah. That is the responsibility of realizing the benefit for the people based on four basic principles: honesty, justice, discipline, and consultation (democracy).